Continuous passive motion using soft actuator for hand rehabilitation - Sii, Zhi Ying, 1995- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Mekatronik)) - Universiti Teknologi Malaysia, 2018